A review on developments of deployable membrane-based reflector antennas. Issue 9 (1st November 2021) - Chandra, Mukesh; Kumar, Satish; Chattopadhyaya, Somnath; Chatterjee, Sayan; Kumar, Prakash
Abstract: The gossamer space structures are very large and ultra-lightweight structures. A large aperture-based space structure is highly efficient in capturing signals from a wide coverage area. However, their deployment in space has been a critical challenge to date. Extensive research has been carried out on various types of gossamer structures used for earth exploration and deep space applications. Space antenna, in general, should have a large electrical aperture, be light in weight with small stowage volume, be easily deployable in space, and thermally stable. The antenna consists mainly of a reflector as a major part and a torus for supporting the reflector, electronic control unit, and struts. This paper covers an extensive review of gossamer space structure considering different categories of large deployable antennas. More attention has been given to a large membrane-based antenna having a parabolic reflector. This work includes the study of designs, analyses, and development of prototypes and successful deployment of space structures in orbit. We emphasize understanding the behaviour of thin membrane, their static and dynamic characteristics, wrinkling control, shape control of thin membrane reflector, and recent advances in deployment techniques of large deployable antenna structures.